1973
DOI: 10.1111/j.1476-5381.1973.tb08532.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the central cardiovascular action of clonidine

Abstract: Summary The fall in arterial blood pressure with bradycardia that occurs on injection of clonidine into the cerebral ventricles and into the cisterna magna is attributed to an action on ‘chemosensitive zones’ situated at the ventral surface of the brain stem. This conclusion is based on the following results obtained in cats anaesthetized with pentobarbitone sodium. The fall in blood pressure no longer occurs on injection of clonidine (10 to 100 μg) into the cerebral ventricles when the passage of clonidine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

1975
1975
2000
2000

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(31 citation statements)
references
References 15 publications
(27 reference statements)
3
27
1
Order By: Relevance
“…As the bilateral area from which vasopressin release was obtained with nicotine lies 6-9 mm caudal to the trapezoid bodies the area is situated more caudally on the ventral surface of the medulla than the bilateral area from where most of the blood pressure effects have been obtained with drugs topically applied through perspex rings (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974;Guertzenstein & Silver, 1974). For pentobarbitone sodium, glycine and clonidine, it was shown that they no longer produced their depressor effects with the rings placed so that their rostral border was 5 mm caudal from the trapezoid bodies, and the glycine-sensitive area was restricted in longitudinal direction to between 1 and 2.5 mm caudal to the trapezoid bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the bilateral area from which vasopressin release was obtained with nicotine lies 6-9 mm caudal to the trapezoid bodies the area is situated more caudally on the ventral surface of the medulla than the bilateral area from where most of the blood pressure effects have been obtained with drugs topically applied through perspex rings (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974;Guertzenstein & Silver, 1974). For pentobarbitone sodium, glycine and clonidine, it was shown that they no longer produced their depressor effects with the rings placed so that their rostral border was 5 mm caudal from the trapezoid bodies, and the glycine-sensitive area was restricted in longitudinal direction to between 1 and 2.5 mm caudal to the trapezoid bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a number of drugs which, on intraventricular injection affect blood pressure, heart rate, respiration or blood glucose, act in this way (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974;Feldberg & Gupta, 1974;Guertzenstein & Silver, 1974;Dey, Feldberg & Wendlandt, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago we demonstrated that, in the cat, the major site for the central hypotensive effect of clonidine was within the nucleus reticularis lateralis (NRL) area of the medulla (Bousquet & Guertzenstein, 1973;Bousquet et al, 1981). More recently, a structure-activity study proved that the imidazolines were able to induce such effects although catecholamines or phenylethylamines could not (Bousquet et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested a centrally mediated pressor action of clonidine (Bousquet and Guertzenstein 1973;Trolin 1975;Kawasaki and Takasaki 1986). We recently observed in conscious rat that the hypotension induced by i.c.v.…”
Section: Discussionmentioning
confidence: 97%
“…yohimbine, and this might suggest the existence of a centrally mediated hypertensive action of clonidine (Imai et al 1986). The existence of a suprabulbar pressor center involving by alpha-adrenergic mechanisms has been suggested by several authors (Przuntek et al 1971;Bousquet and Guertzenstein 1973;Korner et al 1981). Trolin (1975) reported that the hypotensive effect of i.v, clonidine in conscious rat was potentiated by pentobarbital anesthesia and decerebration, and concluded that a pressor effect of clonidine, mediated by a suprabulbar pressor center was easily suppressed by pentobarbital anesthesia.…”
Section: Discussionmentioning
confidence: 99%